Monitoring the composition and evolution of the research networks of the CGIAR Research Program on Roots, Tubers and Bananas (RTB) - Ekboir, Javier M.; Blundo Canto, Genowefa M.; Sette, Cristina (2013)
Several tools have been developed in the last three decades to manage not-for-profit research activities. Most of these tools have focused on research outputs or outcomes, while few have analysed the processes of research and innovation to identify emerging problems and opportunities during the course of a project. This brief presents a cost-effective methodology that can be used to monitor changes in research networks. Since these networks change as the research projects mature (Kratzer, Gemuenden and Lettl, 2008), tracking the network structure provides information on the nature and evolution of research activities.